If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2x = 4x + -13 Reorder the terms: 5 + 2x = -13 + 4x Solving 5 + 2x = -13 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 2x + -4x = -13 + 4x + -4x Combine like terms: 2x + -4x = -2x 5 + -2x = -13 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -2x = -13 + 0 5 + -2x = -13 Add '-5' to each side of the equation. 5 + -5 + -2x = -13 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = -13 + -5 -2x = -13 + -5 Combine like terms: -13 + -5 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 4n+6+-2n=2(n+3) | | 5x+9*0=45 | | 1+6.33z=-2.5 | | 0.062=-0.06m-0.01 | | x^2-20=-125 | | 85=-5(2r-7) | | 4(3-2n)=n+66 | | -4m-7(6-2m)=22 | | 5*0+9y=45 | | .33x=1.33 | | 8y-12-4y+9=0 | | 8y+7=4y-29 | | 9(4-2x)=3(2-6x) | | 15x^2-50x=0 | | 5x-4x=-6+3 | | 0.60x+0.30(70)=0.30(148) | | h/3+h/6=1 | | 7y-20=-2y-47 | | 9=-4.3 | | -6+6n=6(10-10n) | | 3m+8=m+18 | | 36p+4j=33 | | 3x^4+21x^3-36x^2+3=0 | | 2g+4h=47 | | 2g*4h=47 | | 3y-11=5y-35 | | 4b=9(b+5) | | -6y+17=-9y-7 | | 7b-10+1+10b=60 | | -3k+14=-4+3k | | 3X^2-3X+10=04 | | 1.6y+3.2=-1.6 |